2011
DOI: 10.3390/s110807625
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Precision Time Synchronization for Wireless Sensor Networks

Abstract: Time synchronization in wireless sensor networks (WSNs) is a fundamental issue for the coordination of distributed entities and events. Nondeterministic latency, which may decrease the accuracy and precision of time synchronization can occur at any point in the network layers. Specially, random back-off by channel contention leads to a large uncertainty. In order to reduce the large nondeterministic uncertainty from channel contention, we propose an enhanced precision time synchronization protocol in this pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…TPSN follows the rules specified in (Ganeriwal et al 2003), focused on tree-based scenarios. Under these circumstances (different from our study focused on the IEEE 802.15.5 standard), the method in (Cho et al 2011) slightly improves the synchronization accuracy under ideal conditions at the expense of increasing the computational complexity. Furthermore, this algorithm does not consider the recovery of synchronization messages in case of loss, therefore worsening the synchronization precision on real implementations.…”
Section: Related Studymentioning
confidence: 65%
See 2 more Smart Citations
“…TPSN follows the rules specified in (Ganeriwal et al 2003), focused on tree-based scenarios. Under these circumstances (different from our study focused on the IEEE 802.15.5 standard), the method in (Cho et al 2011) slightly improves the synchronization accuracy under ideal conditions at the expense of increasing the computational complexity. Furthermore, this algorithm does not consider the recovery of synchronization messages in case of loss, therefore worsening the synchronization precision on real implementations.…”
Section: Related Studymentioning
confidence: 65%
“…In a recent article (Cho et al 2011), a synchronization method was presented and evaluated for a grid topology, a particular scenario of the mesh arrangement. This algorithm improves the Light-Weight Time Synchronization (LWTS) schemes, removing some of the duplicated broadcast messages occurring in the flooding phases of the topology construction, children discovery, and synchronization operation.…”
Section: Related Studymentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, control command depends on synchronous monitoring data of each node in various networks [1][2][3]. Therefore, clock synchronization plays an important role in these systems [4][5].…”
Section: Introductionmentioning
confidence: 99%
“…The study showed that the system is able to detect all the failures injected on the master under different conditions and correctly identify failures on slaves with a high probability. Cho et al [11] proposed enhanced precision time synchronization for wireless sensor networks (WSNs). Valls et al [12] proposed an enhanced middleware for real-time reconfiguration of service-oriented distributed real-time systems.…”
mentioning
confidence: 99%